Proceedings of the First Workshop on NLP and Computational Social Science 2016
DOI: 10.18653/v1/w16-5613
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an Annotated Corpus for Protest Event Mining

Abstract: We present a corpus for protest event min-ing that combines token-level annotation with the event schema and ontology of entities and events from protest research in the social sci-ences. The dataset uses newswire reports from the English Gigaword corpus. The token-level annotation is inspired by annotation standards for event extraction, in particular that of the Automated Content Extraction 2005 corpus (Walker et al., 2006). Domain experts perform the entire annotation task. We report competi-tive intercoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…For instance, the phenomena such as "bandh" and "dharna" are protest event types that are specific to India, and thus, are not covered by any general-purpose protest keywords list. Our evaluation of four keyword lists, which are utilized by Huang et al [25], Wang et al [12], Weidmann and Rød [4], and Makarov et al [26], yielded .68 and .80 precision and recall on our randomly sampled batches at best.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, the phenomena such as "bandh" and "dharna" are protest event types that are specific to India, and thus, are not covered by any general-purpose protest keywords list. Our evaluation of four keyword lists, which are utilized by Huang et al [25], Wang et al [12], Weidmann and Rød [4], and Makarov et al [26], yielded .68 and .80 precision and recall on our randomly sampled batches at best.…”
Section: Methodsmentioning
confidence: 90%
“…Consequently, protest-event specific annotation schemas and data sets were proposed for creating automated or semi-automated event knowledge bases [4,11,24,25]. In their corpus, Makarov et al [26] used the ontology of CP events which is very similar to ours and identified ten event types. They coded event actors and issues that correspond to each event.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Many research teams interested in accurately capturing more detailed characteristics of protests have concluded that the best approaches for now are semi-automated or hybrid workflows that automate the pre-processing of articles to filter out irrelevant articles but rely on human coders at the final steps of identifying and coding events within articles. Major examples include Mass Mobilization in Autocracies (Croicu and Weidmann 2015;Hellmeier, Rød and Weidmann 2019;Weidmann and Rød 2018), the Cline Center's SPEED (Nardulli, Althaus and Hayes 2015), the Zurich-based team studying European protests (Lorenzini et al 2021;Makarov, Lorenzini and Kriesi 2016), Armed Conflict Location and Event Data (ACLED) 5 , Count Love (Leung and Perkins 2021) and Crowd Counting Consortium (CCC) (Fisher et al 2019).…”
Section: Protest Event Methodsmentioning
confidence: 99%
“…Many research teams interested in accurately capturing the characteristics of protests have concluded that the best approaches for now are semi-automated or hybrid workflows that automate the pre-processing of articles to filter out irrelevant articles but rely on human coders at the final steps of identifying and coding events within articles. Major examples include the Mass Mobilization in Autocracies project (Croicu and Weidmann 2015, Hellmeier, Rød and Weidmann 2019, the Cline Center's SPEED project (Nardulli, Althaus and Hayes 2015) and the Zurich-based team interested in political contestation in Europe (Lorenzini et al 2021, Makarov, Lorenzini andKriesi 2016). Our own project has a similar orientation to these hybrid projects and was developed concurrently with them.…”
Section: Protest Event Studiesmentioning
confidence: 99%